Wind turbine and ice breaking - Nilsen, Peter Tor Furseth (UiT Norges arktiske universitet, 2019)
The arctic climate imposes the challenge of ice accretion on the blades of the wind turbine created by the atmospheric ice. Over time, the ice build-up causes ice shedding which can do structural damage to the wind turbine. The process involving ice breaking and shedding is not well understood. This document explains the mechanical properties of ice such as density, coefficient of thermal expansion, elastic modulus and structural build-up of ice. In understanding of ice breaking, ice deformation is explained on how ice deforms elastically, plastically and by brittle fracture. The properties of ice failure are mentioned as well as the three regimes; ductile, transitional and brittle regime. The brittle regime of ice failure are further split into three categories; intermittent, lock-in and continuous brittle crushing. This is based on the speed range of development of ice force and the structure response. Simulations are done to understand how deflection, as well as lift and drag, acts for the blade in regards of wind direction and gravitational force. For this, a model of a wind turbine blade is made in Inventor and analyzed in Ansys. An understanding of what materials is used for wind turbine blades is mentioned with its desired properties and build-up.